Cytokine response to resistance exercise in children with excess adiposity and Prader‐Willi syndrome - Vincent Vuong; Andrea M. Haqq; Daniela A. Rubin (Physiological Reports)
Abstract Interleukin‐6 (IL‐6), tumor necrosis factor alpha (TNF‐α), and irisin (cytokines) are affected by excess body fat (obesity), skeletal muscle, and resistance exercise (RE). The purpose of this study is to determine whether Prader‐Willi Syndrome (PWS), a genetic cause for obesity (OB), or non‐syndromic OB influences these cytokine responses to RE. Nine children with PWS (11.4 ± 3.3 years, 45.6 ± 5.2% BF), 11 children without OB (9.2 ± 1.4 years, 18.6 ± 5.0% BF), and 12 children with OB (9.6 ± 1.3 years, 40.4 ± 5.4% BF) participated. Children stepped onto an elevated platform wearing a weighted vest for 6 sets of 10 repetitions per leg separated by 1 min of rest. Blood samples were obtained before exercise (pre), immediately post (IP), and during recovery (+15 and +60 min). There were no group‐by‐time interactions for any cytokine; and neither time nor group effects for TNF‐α or irisin (p ≥ 0.378). For IL‐6, 60+ was higher than pre, IP, and +15 (p < 0.001). Children with PWS and OB had increased IL‐6 than children without OB (p ≤ 0.038). Neither PWS nor OB affected IL‐6, TNF‐α or irisin responses to RE. However, excess body fat was associated with higher IL‐6 concentrations.